One pot conversion of glycerol to lactic acid on copper based catalysts - Jose - Chimentao; Ricardo (2023)
DISCLOSURE SUMMARY: Describe in simple terms the main objectives of your project and the obtained results. Use an appropriate language so as for the understanding of non-specialists in the field. This information may be published in CONICYT's web page. The maximum length of this section is 1 page (font size 10 Arial or Verdana). Today's chemical industry relies heavily on fossil resources as feedstock, resulting in a linear extract-make-use-dispose economic model. As a result of anthropogenic activity, mainly associated with the use of fossil resources, environmental sustainability and the depletion of energy sources have become a critical situation today. In this context, biomass has been widely recognized in the field of academic research and industry as a potential renewable energy resource capable of providing a partial solution to these problems, with the production of biodiesel being one of the purposes for which it has been used to achieve that purpose. The biodiesel industry became the main producer of glycerol, whose accumulation has come to exceed global demand and given that the biodiesel economy depends heavily on the glycerol market. Efforts have been focused on the valorization of this by-product, where the catalytic conversion processes of glycerol have become more relevant. Currently, glycerol has become an outstanding platform molecule for obtaining various chemical compounds that are highly relevant for the chemical industry. Thus, glycerol became a building block to produce a variety of compounds to replace other high-cost raw materials. In this research work, the catalytic transformation of glycerol to value-added compounds was evaluated on copper-based catalysts supported on mesoporous materials of the SBA-15 type. The conversion of glycerol was evaluated in two steps: Step 1 Dehydration of glycerol to hydroxyacetone (HA) and Step 2 Selective oxidation of HA to lactic acid (LA) or derivates. The active phase of copper is ideal because it preferentially breaks the bonds of glycerol to the ...